Lived Experience in New Models of Care for Substance Use Disorder: A Systematic Review of Peer Recovery Support Services and Recovery Coaching - Eddie, David; Hoffman, Lauren; Vilsaint, Corrie; Abry, Alexandra; Bergman, Brandon; Hoeppner, Bettina; Weinstein, Charles; Kelly, John F. (Frontiers in Psychology, 2019)
Peer recovery support services (PRSS) are increasingly being employed in a range of clinical settings to assist individuals with substance use disorder (SUD) and co-occurring psychological disorders. PRSS are peer-driven mentoring, education, and support ministrations delivered by individuals who, because of their own experience with SUD and SUD recovery, are experientially qualified to support peers currently experiencing SUD and associated problems. This systematic review characterizes the existing experimental, quasi-experimental, single- and multi-group prospective and retrospective, and cross-sectional research on PRSS. Findings to date tentatively speak to the potential of peer supports across a number of SUD treatment settings, as evidenced by positive findings on measures including reduced substance use and SUD relapse rates, improved relationships with treatment providers and social supports, increased treatment retention, and greater treatment satisfaction. These findings, however, should be viewed in light of many null findings to date, as well as significant methodological limitations of the existing literature, including inability to distinguish the effects of peer recovery support from other recovery support activities, heterogeneous populations, inconsistency in the definitions of peer workers and recovery coaches, and lack of any, or appropriate comparison groups. Further, role definitions for PRSS and the complexity of clinical boundaries for peers working in the field represent important implementation challenges presented by this novel class of approaches for SUD management. There remains a need for further rigorous investigation to establish the efficacy, effectiveness, and cost-benefits of PRSS. Ultimately, such research may also help solidify PRSS role definitions, identify optimal training guidelines for peers, and establish for whom and under what conditions PRSS are most effective.